Keratocystic odontogenic tumor: Role of cone beam computed tomography and magnetic resonance imaging - De Oliveira Gamba, Thiago; Flores, Isadora Luana; Pinto, Antonione Bezerra; Costa, Andre Luiz; Moraes, Mari Eli [UNESP]; Lopes, Sérgio Lucio [UNESP] (My University, 2016)
Keratocystic odontogenic tumors (KCOTs) are known for unique and varied behavior, high recurrence rates, and distinctive histopathologic findings. Differential diagnosis and management of KCOTs may be challenging because other jaw lesions may present similar characteristics. Careful interpretation of cone beam computed tomograms and magnetic resonance images has great significance for precise assessment of KCOTs and their relationships to adjacent anatomic structures as well as for treatment planning. This case report describes a KCOT that developed in the left angle and mandibular ramus in association with a semierupted third molar.
Keywords: Cone beam computed tomography; Keratocystic odontogenic tumor; Magnetic resonance imaging; Odontogenic keratocyst; Oral diagnosis